2016
DOI: 10.1089/vbz.2016.2017
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing and Phylogenetic Analysis of a Getah Virus Strain (GenusAlphavirus, FamilyTogaviridae) Isolated fromCulex tritaeniorhynchusMosquitoes in Nagasaki, Japan in 2012

Abstract: Getah virus (GETV; genus Alphavirus, family Togaviridae) is a mosquito-borne virus known to cause disease in horses and pigs. In 2014, for the first time in ∼30 years, a sudden GETV outbreak occurred among racehorses in Ibaraki, Japan. Two years before this outbreak, we obtained multiple GETV isolates from Culex tritaeniorhynchus mosquitoes collected in Nagasaki, Japan and determined the whole genome sequence of GETV isolate 12IH26. Our phylogenetic analysis of GETV strains revealed that the isolate 12IH26 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The phenomenon of this virus spread has also occurred in Getah virus (genus Alphavirus, family Togaviridae). A study reported the virus being transported in the same direction from west Japan into central Japan, with possible routes of transportation, such as bird migration and windblown mosquitoes [56].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of this virus spread has also occurred in Getah virus (genus Alphavirus, family Togaviridae). A study reported the virus being transported in the same direction from west Japan into central Japan, with possible routes of transportation, such as bird migration and windblown mosquitoes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis showed that strain 15-I-1105 was located in the same cluster as the strains isolated from horses during the 2014 outbreak (14-I-605-C1, 14-I-605-C2), one strain isolated from a horse during the 2015 outbreak (15-I-752), and one strain isolated from mosquitoes in Nagasaki Prefecture in 2012 (12IH26, [14]) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenetic analysis of various Getah virus strains revealed that the strain from a pig (15-I-1105) and strains from recent outbreaks in horses (14-I-605-C1, 14-I-605-C2, and 15-I-752) formed a cluster with a strain isolated from mosquitoes in Nagasaki Prefecture in 2012 (12IH26, [14]) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An epidemic occurred at the same location in 2016. In addition, Getah viruses were isolated from mosquitoes in 2012 ( 7 ) and pigs in 2015 ( 8 ). Here, we read the complete genome sequences of the strains isolated from horses in 2016 and compared them with those of the strains recently isolated from horses, pigs, and mosquitoes.…”
Section: Genome Announcementmentioning
confidence: 99%